Strengthening Family Commitment in Monitoring Child Development through the Role of Filial Values - Sri Utami; Rekawati Susilaningrum; Evi Yunita (Health Dynamics, 2025)
Background: Monitoring the development of children under five by families is essential for optimal child development. Family commitment in this context is influenced by various factors, including personal factors and family resources. This study aims to analyze the influence of monitoring on child development, with a focus on the role of filial values as a mediator variable. Methods: This study used an explanatory, cross-sectional design. The sample consisted of 275 families with toddlers within the health center working area in Surabaya City, selected through simple random sampling. The variables assessed include factors influencing family commitment. Data were collected using a questionnaire and analyzed using SEM-PLS. Results: The findings showed that personal factors and resource factors significantly influence family commitment to monitoring the development of children under five, mediated by the filial values. The coefficient for the effect of personal factors on behavioral factors was 0.149 (p = 0.028); for resource factors on cognition behavior, 0.541 (p = 0.000); for cognition behavior on filial values, 0.493 (p = 0.000); for cognition behavior on commitment, 0.1113 (p = 0.024); and for filial values on commitment, 0.697 (p = 0.000). Conclusions: Filial values play a crucial role in enhancing the impact of personal factors and family resources on family commitment to monitoring the child development. Further research is needed on an intervention that strengthens the filial value of families to enhance family commitment to optimizing the monitoring of children’s development. Personal factors and family resources are key in shaping family commitment, with filial values strengthening this relationship. Emphasizing personal aspects, family resources, and filial values is essential to increase family commitment in monitoring child development.